Effect size odds ratio on management control system and organizational performance - Nahar, Aida; Tri Jatmiko Wahyu Prabowo, Anis Chariri, (Opción, 2019)
This study is a meta-analysis study, which has been conducted using the effect size odds ratio method that examines the effect of management control systems (MCS) on organizational performance. The data were analyzed using a random effect model with the Review Manager 5.3 (RevMan 5.3) software. This study found that management control systems positively and significantly influence organizational performance. In conclusion, a company must pay attention to the management control system in managing the company so that the company’s ideal performance can be successfully achieved.